Some Ecology Aspect of Kulari Fish (Lobocheilos falcifer C.V Cyprinidae) in Batang Kuranii River, Padang, West Sumatra - Kadifi, Yusrika Ika; Zakaria, Indra Junaidi; Efrizal, Efrizal (Metamorfosa: Journal of Biological Sciences, 2019)
This research was carried out.in January-June 2013. This research aimed to analyze some ecological aspects (habitat, body length, distribution, growth pattern) in Kulari fish ( Lobocheilos falcifer C.V : Cyprinidae) at Batang Kuranji river, Padang. This studied use survey method with stratified random sampling technique (at three locations) to collected samples. The result of this study showed that water temperature has 26,55 0 C; pH 5,6; O 2 5,78 mg/l; BOD 5 0,79mg/l; CO 2 1,81 mg/l; TSS 0, 51; depth 40.88 cm, and current velocity 0.50 m/s. The growth patterns of kulari fish showed that male fishes were in negative allometric and female fishes were in isometric. Keyword: Ecology aspects, Kulari fish ( Lobocheilos falcifer ), Batang Kuranji River